KEIDIOMATISAN KOMPOSITUM BERLEKSIKON HATI DALAM BAHASA INDONESIA - Rovita, Dien; Suganda, Sonya Puspasari; Yuwono, Untung (Paradigma: Jurnal Kajian Budaya, 2025)
A compound (kompositum) is a construction formed through word formation by combining two or more elements to create a new meaning. In Indonesian, compounds can be formed by combining several elements, one of which may be a nominal lexeme referring to a body part. Compound words can be distinguished from other word combinations—particularly syntactic phrases—based on grammatical and semantic criteria. Semantically, compounds can be analyzed according to the degree of idiomaticity in their meanings. Based on this premise, the present study aims to explain the idiomaticity of compounds in Indonesian that are formed by combining multiple elements, one of which is a body part lexeme, specifically compounds containing the lexeme hati(heart). This study on Indonesian compounds is a qualitative research project conducted through corpus analysis, utilizing the Indonesian Web as Corpus (IndonesianWac) available on the Sketch Engine corpus tool (http://www.sketchengine.co.uk/indonesian-wac/). The analysis of compound idiomaticity can be carried out using criteria such as lexical and grammatical variability, literality, compositionality versus non-compositionality, and predictability. Based on these criteria, a number of compounds containing the lexeme hati were identified and categorized as idiomatic compounds, semi-idiomatic compounds, and non-idiomatic compounds.